2017
DOI: 10.1103/physrevb.95.144404
|View full text |Cite
|
Sign up to set email alerts
|

Properties of spin-12triangular-lattice antiferromagnetsCuY2Ge2O8andet al.

Abstract: Keyword: low-dimensional quantum spin system, geometrical frustration, magnetic long-range order, field induced phase transition, charge transfer insulator.PACS Numbers: 75.10.Jm, 75.30.Kz, Abstract: We found new two-dimensional (2D) quantum (S=1/2) antiferromagnetic systems: CuRE2Ge2O8 (RE=Y and La).According to our analysis of high-resolution X-ray and neutron diffraction experiments, the Cu-network of CuRE2Ge2O8 (RE=Y and La) exhibits a 2D triangular lattice linked via weak bonds along the perpendicular b-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 61 publications
(96 reference statements)
1
16
0
2
Order By: Relevance
“…We collected altogether 2889 Bragg peaks (1860 independent Bragg peaks). The crystal structure was refined using the I 1 m 1 unit cell setting of the nonmagnetic rare-earth analog [38]. The unit cell size is a( (9), and V ( Å3 )=661.2(3).…”
Section: Experimental Results and Analysis A Structural Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We collected altogether 2889 Bragg peaks (1860 independent Bragg peaks). The crystal structure was refined using the I 1 m 1 unit cell setting of the nonmagnetic rare-earth analog [38]. The unit cell size is a( (9), and V ( Å3 )=661.2(3).…”
Section: Experimental Results and Analysis A Structural Analysismentioning
confidence: 99%
“…Fig. 2 shows the refined crystal structure of the CuNd 2 Ge 2 O 8 system, which is isostructural with other rare-earth systems including the nonmagnetic rare-earth analog Cu(Y/La) 2 Ge 2 O 8 [38]. The unit cell size and monoclinic β angle vary depending on the ionic size of RE 3+ [39].…”
Section: Experimental Results and Analysis A Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3(i) and 3(j). An explanation for this behavior may come from a theoretical study by Kohno et al [38] which considers the spin excitation spectra of 2D triangular lattice compounds, such as Cs 2 CuCl 4 [39] and Cu(Y/La) 2 Ge 2 O 8 [40], with magnetic couplings close to the limit of 1D spin chains. Kohno et al showed that (FM or AFM) interchain interactions between the 1D spin chains introduces an (attractive or repulsive) force between spinons, resulting in delocalized composite particles called (bound or anti-bound) triplons which can move coherently between chains [41].…”
Section: Temperature Dependencementioning
confidence: 99%